Collapse Behavior and Energy Absorption Characteristics of Design Multi-Cell Thin Wall Structure 3D-Printed Under Quasi Statistic Loads - Willy Artha Wirawan; Bambang Junipitoyo; Setyo Hariyadi Suranto Putro; A’yan Sabitah; Ahmad Hamim Suudy; Ridwan Ridwan; Moch. Agus Choiron (Universitas Muhammadiyah Magelang, 2024)
Crashworthiness is a passive device that has an important function as an absorbing component of the impact energy resulting from an accidental event. The main problem in the crashworthy design is the dimensional limitation on the front end of the vehicle with the driver so that most of the energy absorption is limited. Besides, the complexity of crashworthiness design is difficult to make conventionally. This research aims to find out the effectiveness of crashworthiness design in energy absorption and the resulting deformation patterns. Crashwortines are made in a multi-cell shape using PLA material and printed using a 3D printing raise machine. Crashworthiness is produced with four variation shapes of a Multi-cell circle (MCC), Multi-Cell square (MCS), Multicell pentagonal (MCP), and Multi-Cell pentagonal circles (MCPC) with a side thickness of 2 mm and a length of 150 mm. Experimental quasi-static testing is carried out in the frontal direction using a UTM machine at an operating speed of 2mm/s. The results of the study show that the design of the crash box of the pentagon circle has a significant increase in the energy absorption value of 62.49%, which can be recommended in future impact resistance tube designs. The characteristics of the deformation pattern and the failure resulting from the crashworthiness tend to form the pattern of the bending lamina failure. Failures can occur due to plastic fold, elastic bend, and pressure deformation mechanisms followed by new folding formations (lobes).